Verba volant, transcripta manent: What corporate earnings calls reveal about the AI stock rally - Michele Ca'Zorzi; Gianluigi Lopardo; Ana-Simona Manu (European Central Bank (ECB), 2025)
This paper investigates the economic impact of technological innovation, focusing on generative AI (GenAI) following ChatGPT's release in November 2022. We propose a novel framework leveraging large language models to analyze earnings call transcripts. Our method quantifies firms' GenAI exposure and classifies sentiment as opportunity, adoption, or risk. Using panel econometric techniques, we assess GenAI exposure's impact on S&P 500 firms' financial performance over 2014-2023. We find two main results. First, GenAI exposure rose sharply after ChatGPT's release, particularly in IT, Consumer Services, and Consumer Discretionary sectors, coinciding with sentiment shifts toward adoption. Second, GenAI exposure significantly influenced stock market performance. Firms with early and high GenAI exposure saw stronger returns, though earnings expectations improved modestly. Panel regressions show a 1 percentage point increase in GenAI exposure led to 0.26% rise in quarterly excess returns. Difference-in-Difference estimates indicate 2.4% average quarterly stock price increases following ChatGPT's release.
Keywords: C80; G14; G30; L25; O33; 330; artificial intelligence; generative AI; ChatGPT; earnings call; equity returns